2012
DOI: 10.2337/db11-0963
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Circulating IGFBP1 Levels Improves Insulin Sensitivity, Promotes Nitric Oxide Production, Lowers Blood Pressure, and Protects Against Atherosclerosis

Abstract: Low concentrations of insulin-like growth factor (IGF) binding protein-1 (IGFBP1) are associated with insulin resistance, diabetes, and cardiovascular disease. We investigated whether increasing IGFBP1 levels can prevent the development of these disorders. Metabolic and vascular phenotype were examined in response to human IGFBP1 overexpression in mice with diet-induced obesity, mice heterozygous for deletion of insulin receptors (IR+/−), and ApoE−/− mice. Direct effects of human (h)IGFBP1 on nitric oxide (NO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 54 publications
4
73
1
Order By: Relevance
“…The ERK/c-Jun pathway may be involved in the induction of IGFBP1 by PL. Vitamin B6 and IGFBP1 are hypothesized as protective factors against cancers and cardiovascular disease (7,15,22,35). Thus, it is of interest to examine whether vitamin B6 intake causes a higher production of IGFBP1 in the liver, resulting in higher circulating IGFBP1, which in turn leads to lower development of these diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ERK/c-Jun pathway may be involved in the induction of IGFBP1 by PL. Vitamin B6 and IGFBP1 are hypothesized as protective factors against cancers and cardiovascular disease (7,15,22,35). Thus, it is of interest to examine whether vitamin B6 intake causes a higher production of IGFBP1 in the liver, resulting in higher circulating IGFBP1, which in turn leads to lower development of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that IGFBP1 may be a tumor suppressor (16)(17)(18)(19). Low serum IGFBP1 levels are associated with a number of chronic diseases, including colon cancer, cardiovascular disease and diabetes (20)(21)(22). A previous study showed that increased circulating IGFBP1 levels improve insulin sensitivity, lower blood pressure and protect against atherosclerosis (22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest IGFBP-1 plays a role as a protective factor against liver injury, type 2 diabetes, hypertension, atherosclerosis, and cancer (23)(24)(25). Adiponectin is also known to be a protective factor against such diseases, including liver injury (26).…”
Section: Discussionmentioning
confidence: 99%
“…Systolic blood pressure was measured using tailcuff plethysmography in conscious mice, as previously described. 15,16 Mice were pre-warmed for 10 minutes in a thermostatically controlled restrainer (CODA2 System, XBP1000; Kent Scientific). Three training sessions were performed during the week before measurements were taken.…”
Section: Myeloid Cell Enumeration Isolation and Transcriptional Profmentioning
confidence: 99%